RELIGION, CIVIC VALUES, AND EQUAL CITIZENSHIP IN THE LIBERAL DEMOCRATIC POLITY - Gill, Emily R. (Politikologija religije, 2013)
Whether religious and other voluntary associations should reflect public values is a subject of controversy. Corey Brettschneider argues that the state should assert its own values of free and equal citizenship, deliberately attempting to transform the beliefs of illiberal groups through court decisions and through selective withdrawal of tax exemptions. I argue, however, that as long as individuals and groups comply with the law, it is not the business of the state to change their beliefs. Moreover, public authority itself does not always exemplify his preferred values. Second, although I oppose direct funding for organizations that oppose public values, determining which organizations espouse the “right” values accords too much power to public authority. Moreover, many associations evolve over time. Finally, the true threat lies in practices that voluntary associations may seek to impose on the larger community.